Susceptibility to Fear of Heights in Bilateral Vestibulopathy and Other Disorders of Vertigo and Balance - Brandt, Thomas; Grill, Eva; Strupp, Michael; Huppert, Doreen (Frontiers in Neurology, 2018)
Aims: To determine the susceptibility to visual height intolerance (vHI) in patients with acquired bilateral vestibulopathy (BVP). The question was whether postural instability in BVP, which is partially compensated for by visual substitution of the impaired vestibular control of balance, leads to an increased susceptibility. This is of particular importance since fear of heights is dependent on body posture, and visual control of balance at heights can no longer substitute vestibular input. For comparison susceptibility to vHI was determined in patients with other vestibular or functional disorders. Methods: A total of 150 patients aged 18 or above who had been referred to the German Center for Vertigo and Balance Disorders and diagnosed to have BVP were surveyed with a standardized questionnaire by specifically trained neurological professionals. Further, 481 patients with other vestibular or functional disorders were included. Results: Susceptibility to vHI was reported by 29% (32 % in females, 25% in males) of the patients with BVP. Patients with vHI were slightly younger (67 vs. 71 years). Seventy percent of those with vHI reported avoidance of climbing, hiking, stairs, darkness, cycling or swimming (84% of those without vHI). Mean age for onset of vHI was 40 years. Susceptibility to vHI was higher in patients with other vertigo disorders than in those with BVP: 64% in those with phobic postural vertigo, 61% in vestibular migraine, 56% in vestibular paroxysmia, 54% in benign paroxysmal positional vertigo, 49% in unilateral vestibulopathy and 48% in Menière’s disease. Conclusions: The susceptibility to vHI in BVP was not higher than that of the general population (28%). This allows two explanations that need not be alternatives but contribute to each other: 1) Patients with a bilateral peripheral vestibular deficit largely avoid exposure to heights because of their postural instability. 2) The irrational anxiety to fall from heights triggers increased susceptibility to vHI, not the objective postural instability. However, patients with BVP do not exhibit increased comorbid anxiety disorders. This view is supported by the significantly increased susceptibility to vHI in other vestibular syndromes, which are characterized by an increased comorbidity of anxiety disorders.